Application of KTH-integrated nursing model in care of patients with multi-drug resistant tuberculosis - Wei, Hanfen (Am J Transl Res, 2021)
Objective: To evaluate the effect of the KTH-integrated nursing model of the knowledge-attitude-belief-practice model (KABP)-transtheoretical model (TTM)-as a health belief model (HBM) in nursing care of patients with multi-drug resistant tuberculosis (MDR-TB). Methods: Using a prospective study method, 102 patients with MDR-TB were randomly divided into two groups according to a random number table. The control group (n=51) received conventional nursing care, and the study group (n=51) received a KTH-integrated nursing model. The sputum negative conversion rate, effective rate of lesion absorption, level of disease cognition, compliance, self-efficacy (general self-efficacy scale, GSES score), healthy behavior (health-promoting lifestyle profile, HPLP), and quality of life (GQOL-74 scale score) were compared between the two groups. Results: Six months after enrollment, the sputum-negative conversion rate, total effective rate of lesion absorption, and total compliance rate of the study group were significantly higher than those of the control group (80.39% vs. 62.75%, 84.31% vs. 66.67%, 96.08% vs. 78.43%, P<0.05). 6 months after enrollment, the treatment plan, etiopathogenesis and harm, precautions, importance of treatment compliance, observation and follow-up, and total score of the study were all significantly higher than those of the control group (P<0.05). Six months after enrollment, the scores of GSES, HPLP and GQOL-74 in the study group were significantly higher than those of the control group (P<0.05). Conclusion: The implementation of a KTH integrated nursing model for patients with MDR-TB was beneficial to promote sputum-negative conversion and lesion absorption, and improved disease awareness, medication compliance, self-efficacy, healthy behavior, and quality of life.